Financial Sector Assessment : Saudi Arabia - World Bank (Washington, DC, 2013)
The capacity of the banking sector to respond to macroeconomic shocks, and regional uncertainties have been strengthened considerably over the past decade. Historically, the operating environment has been volatile as a result o f pervasive dependence on the hydrocarbon sector and swings in investor confidence associated with uncertainty in the region. This experience has helped shape fairly risk-averse portfolios: the bank-led financial system has functioned with substantial capital-adequacy ratios (CAR), loan-loss provisions, and liquidity buffers. The sector is highly profitable, with returns on assets averaging above 2 percent, supported by a large, low-cost demand deposit base. These buffers are underpinned by an effective regulatory and supervisory structure that proactively contains risk taking through the use o f maximum loan-deposit ratios, caps on individual and corporate indebtedness, and pre-approval requirements on foreign lending. The sector is supported by a modem and efficient payment and settlement infrastructure.